Overexpression of DEC1 in the epithelium of OSF promotes mesenchymal transition via activating FAK/Akt signal axis. (19th September 2022) - Hu, Xin; Wang, Weiming; Hu, Yue; Chen, Wenxin; Wang, Can; Yang, Liudi; Mao, Ting; Xia, Kun; Min, Anjie; Xiong, Haofeng; Su, Tong
Abstract: Background: Previous studies on oral submucous fibrosis (OSF) mostly focused on the activation of fibroblasts and collagen metabolism, while little involved in the epithelium. As we have reported the role of differentiated embryo‐chondrocyte expressed gene 1 (DEC1) in oral cancer and other precancerous lesions, this research aimed to explore its role in the OSF epithelium. Methods: Expression of DEC1 and other proteins were investigated in tissue array constructed with 33 OSF and 14 normal oral mucosa (NOM) tissues. Human oral keratinocytes treated with arecoline and/or hypoxia were used to simulate OSF epithelium and detected for morphological and protein alterations. Inhibition of DEC1 was used to explore its mediating role. Finally, animal models of OSF constructed by locally arecoline injecting in buccal mucosa were used to verify our findings. Results: DEC1 overexpression could be detected in the epithelium of OSF compared with that in NOM followed by phosphorylated FAK and Akt, and DEC1 showed a significant positive correlation with them. Cytology experiment revealed that OSF‐like treatment could upregulate DEC1 expression followed by phosphorylated FAK, Akt, but inhibit E‐cadherin, while knockdown of DEC1 could suppress the effects. In addition, OSF mice revealed higher expression of DEC1 in the epithelium of buccal mucosa, along with synchronized alterations of phosphorylated FAK and Akt. Conclusion: In the epithelium of OSF, overexpression of DEC1 induced activation of FAK/Akt signal axis, caused mesenchymal transition in epithelial cells, and may promote malignant transformation of OSF. Targeting DEC1 in OSF could be promising a new target for the diagnosis and treatment of this process.